Efek Penambahan Protaktinium-231 (Pa-231) pada Nilai Faktor Multiplikasi Efektif Reaktor PWR Berbahan Bakar ThN-U233N - Ratna Dewi Syarifah; Meirita Dwi Afriani; Wenny Maulina; Fajri Prasetya (Program Studi Pendidikan Fisika, UIN Raden Fatah Palembang, 2023)
This study aims to determine the optimum percentage of addition of protactinium-231 in a ThN-U233N fueled PWR reactor.In ThN-U233N, uranium-233 is used as the fissile material. Pa-231 as burnable poisson is added to ThN-U233N fuel to reduce the keff value. In this research conducted benchmarking keff values ​​of OpenMC and SRAC codes, homogeneous and heterogeneous core configurations, and the addition of Pa-231 in ThN-U233N fuel. Neutronic analysis was performed using the OpenMC code. In the homogeneous core configuration, the enrichment percentage of U-233 is varied by 1%-15%. Meanwhile, the heterogeneous core configuration uses 3 variations of ring geometry and fuel. The results of the benchmarking of the OpenMC and SRAC code keff values ​​show a maximum error of 1,906%. The homogeneous core configuration produces the optimum value for U-233 enrichment of 3%. Meanwhile, the optimum value of the heterogeneous core configuration is achieved in ring geometry F1 = F2 = F3 = 3 rings with enrichment of U-233 at F1 = 0,5%, F2 = 3%, F3 = 5,5% and addition of Pa-231 of 1.5%. The optimum calculation results has an excess reactivity value 8.37%.